A UML Profile for Security and Code Generation - Abdellatif Lasbahani; Mostafa Chhiba; Abdelmoumen Tabyaoui (Institute of Advanced Engineering and Science, 2018)
Recently, many research studies have suggested the integration of safety engineering at an early stage of modeling and system development using Model-Driven Architecture (MDA). This concept consists in deploying the UML (Unified Modeling Language) standard as aprincipal metamodel for the abstractions of different systems. To our knowledge, most of this work has focused on integrating security requirements after the implementation phase without taking them into account when designing systems. In this work, we focused our efforts on non-functional aspects such as the business logic layer, data flow monitoring, and high-quality service delivery. Practically, we have proposed a new UML profile for security integration and code generation for the Java platform. Therefore, the security properties will be described by a UML profile and the OCL language to verify the requirements of confidentiality, authorization, availability, data integrity, and data encryption. Finally, the source code such as the application security configuration, the method signatures and their bodies, the persistent entities and the security controllers generated from sequence diagram of system’s internal behavior after its extension with this profile and applying a set of transformations.